Dynamics of the Formation of the Nitrogen-Vacancy Center in Diamond. (1st February 2016) - Silverman, Amihai; Adler, Joan; Kalish, Rafi
Abstract: We present results of simulations of the energetics and dynamics involved in the realization of the NV (nitrogen-vacancy) center in diamond. We use the self-consistent charge-density functional tight-binding approximation and show that when the nitrogen resides on a single substitutional site, it fails to attract a vacancy, hence no NV center can be formed. However, if it occupies a split interstitial site and two vacancies reside on the second or third neighbor sites, an NV center will form following annealing at temperatures as low as 300°C and 650°C, respectively. These results provide guidelines to experimentalists on how to increase the efficiency of NV formation in diamond.